Synthesis of Si(IV)- and Ge(II)-substituted amines, hydrazone, and hydrazine from hypersilyl germylene - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2023)
This study investigates the reactivity of a hypersilyl germylene [PhC-(NtBu)(2)GeSi-(SiMe3)(3)] (1) with various organic compounds including azides, diazoalkanes, 1,2-diphenylhydrazine, and trifluoroacetophenone. The reactivity observed in these reactions is driven by the insertion of the organic fragment between a silicon and germanium bond. This leads to the formation of novel compounds, including an amine featuring three different substituents from three different elements of group 14. When reacting with Me3SiCHN2, we observed the insertion of the diazoalkane fragment in an end-on fashion into the Ge-Si bond. An analogous trend was observed in reactions with 1,2-diphenylhydrazine and trifluoroacetophenone, where the N-N and C-O fragments were inserted into the Ge-Si bond. Multinuclear NMR and single-crystal X-ray diffraction analyses were conducted to characterize the newly synthesized compounds.